2009
DOI: 10.1590/s0100-879x2009001100017
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration is reduced by high tidal volume ventilation in an in vivo healthy rat model

Abstract: Mechanical ventilation has been associated with organ failure in patients with acute respiratory distress syndrome. The present study examines the effects of tidal volume (V T) on renal function using two V T values (8 and 27 mL/kg) in anesthetized, paralyzed and mechanically ventilated male Wistar rats. Animals were randomized into two groups of 6 rats each: V T8 (V T, 8 mL/kg; 61.50 ± 0.92 breaths/min; positive end-expiratory pressure, 3.0 cmH2O; peak airway pressure (PAW), 11.8 ± 2.0 cmH2O), and V T27 (V T,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In a recent study (16) conducted in our laboratory with healthy Wistar rats, we demonstrated that, after 120 min of mechanical ventilation at a low tidal volume (8 ml/kg BW), GFR remained unchanged in relation to baseline values. However, when we used a high tidal volume (27 ml/kg BW), GFR decreased after 60 min on mechanical ventilation, the reduction becoming more marked after 90 min (16). It is well established that mechanical ventilation can worsen renal hemodynamics and function (15), mainly when high volumes and high PEEP are used.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent study (16) conducted in our laboratory with healthy Wistar rats, we demonstrated that, after 120 min of mechanical ventilation at a low tidal volume (8 ml/kg BW), GFR remained unchanged in relation to baseline values. However, when we used a high tidal volume (27 ml/kg BW), GFR decreased after 60 min on mechanical ventilation, the reduction becoming more marked after 90 min (16). It is well established that mechanical ventilation can worsen renal hemodynamics and function (15), mainly when high volumes and high PEEP are used.…”
Section: Discussionmentioning
confidence: 71%
“…At the end of experiment, the rats were anesthetized with 50 mg/ kg.bw sodium pentobarbital intraperitoneally [19]. Blood samples were obtained directly from the heart by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%